Adventitious Root Formation in Grewia optiva J.R. Drummond ex. Burret : Effects of IBA and Pre-severance Treatment on Rooting Response - Bhardwaj, Anita; Bhardwaj, D.R.; Mishra, V.K. (Indian Journal of Agroforestry, 2020)
In Grewia optiva application of IBA, pre-severance treatment and IBAx pre-severance interaction effects were significantly related to rooting percent, number of roots per cutting and survival percentage. The best rooting response (29.44 %), roots per cutting (4.44), root length (B.66 cm), sprout length (5.0 cm) and survival percentage (29.44) was recorded at O.B% IBA level. In pre-severance treatment, maximum rooting (36.67%), roots per cutting (B.O), primary root length (1B.0 cm), sprout length (B.46 cm) and survival percentage (36.67) was recorded in ringed plus tapped propagules. Similarly, in the interaction effects between IBA and pre-sevrance treatment, maximum rooting (60%), primary root number (1.67), root length (22.0 cm) and survival percentage (60) were recorded in ringed plus tapped propagules treated at O.B% IBAand its difference from all other treatment combinations, in general, and control in particular was found to be significant.